2011
DOI: 10.3109/10428194.2011.584006
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial with melphalan and prednisone versus melphalan and prednisone plus thalidomide in newly diagnosed multiple myeloma patients not eligible for autologous stem cell transplant

Abstract: Several trials comparing the efficacy of standard melphalan and prednisone (MP) therapy with MP plus thalidomide (MPT) in elderly patients with multiple myeloma (MM) have been reported, with inconsistent results. The primary goal of our study was to evaluate the efficacy and toxicity of MP versus MPT in newly diagnosed patients with MM who were transplant-ineligible or over age 65. A total of 135 patients were enrolled. Either minimal response or better or partial response or better were more frequent with MPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…[5,[16][17][18]33,38,35] Although no NMA was conducted on safety outcomes, the proportion of patients discontinuing treatment due to AEs and the reported grade 3/4 AEs from the 11 studies included in the sensitivity analysis was overall higher in triplet combinations compared with doublets. [16][17][18] Similar results were observed in the FIRST trial, where 44% of patients randomized to MPT reported grade 3/4 neutropenia compared with 28% in the Rd until progression group [5]. Where reported, grade 3/4 neuropathic events were consistently higher in patients receiving triplet versus doublet regimens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5,[16][17][18]33,38,35] Although no NMA was conducted on safety outcomes, the proportion of patients discontinuing treatment due to AEs and the reported grade 3/4 AEs from the 11 studies included in the sensitivity analysis was overall higher in triplet combinations compared with doublets. [16][17][18] Similar results were observed in the FIRST trial, where 44% of patients randomized to MPT reported grade 3/4 neutropenia compared with 28% in the Rd until progression group [5]. Where reported, grade 3/4 neuropathic events were consistently higher in patients receiving triplet versus doublet regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In this SLR, the evidence networks consisted of a limited number of studies relative to the number of treatments under consideration and nearly all connections in the networks consisted of single trials. Additionally, included studies comparing MPT versus MP, [16][17][18] showed no heterogeneity (I 2 ¼ 0%). Thus, a fixed effect model was considered the most appropriate analysis.…”
Section: Network Meta-analysismentioning
confidence: 97%
See 3 more Smart Citations